The Influence Of Customer Satisfaction And Trust On Customer Loyalty In Citilink Indonesia Airline - Rizky Ahmad Sya’bana; Totok Sugiharto (Cakrawala Repositori IMWI, 2024)
This study aims to analyze the influence of customer satisfaction on customer loyalty in Citilink Indonesia airline, with customer trust as a mediator variable. The research method employed a quantitative approach with a sample size of 150 respondents gathered through a survey questionnaire distributed to Citilink Indonesia passengers. The study focused on three main variables: customer satisfaction, customer trust, and customer loyalty. Data analysis utilized regression techniques to assess the relationship between customer satisfaction and customer loyalty, as well as the mediating role of customer trust in this relationship. The research findings indicate that customer satisfaction significantly and positively influences customer loyalty. Moreover, customer trust has been proven effective in mediating the relationship between customer satisfaction and customer loyalty.